Testing histological images of mammary tissues on compatibility with the Boolean model of random sets - Mrkvička, Tomáš (Image analysis and stereology, 2011)
Methods for testing the Boolean model assumption from binary images are briefly reviewed. Two hundred binary images of mammary cancer tissue and 200 images of mastopathic tissue were tested individually on the Boolean model assumption. In a previous paper, it had been found that a Monte Carlo method based on the approximation of the envelopes by a multi-normal distribution with the normalized intrinsic volume densities of parallel sets as a summary statistics had the highest power for this purpose. Hence, this method was usedhere as its first application to real biomedical data. It was found that mastopathic tissue deviates from the Boolean model significantly more stronglythan mammary cancer tissue does.
Keywords: Breast Neoplasms; Dojka, novotvorbe; Pathology; Slika, obdelava z računalnikom; Slučajnost, razporeditev; Image Processing, Computer-Assisted; Monte Carlo, metoda; Random Allocation; stereologija; Monte Carlo Method; rak dojke; metoda Monte Carlo